2013
DOI: 10.3109/02770903.2013.822079
|View full text |Cite
|
Sign up to set email alerts
|

Fragrance materials in asthma: a pilot study using a surrogate aerosol product

Abstract: A trend for increased symptoms was noted in moderate asthmatics, suggesting that asthma severity may play a factor in fragrance sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This therapy was found to be superior when compared to synthetic odors. Synthetic fragrances generally contain irritants, like solvents and propellants causing irritation in some people [23][24][25]. According to aroma therapists, synthetic odor does not match the importance of essential oils as they are deficient in natural or vital energy; however, this has been remained a matter of debate between odor psychologists and biochemists [26] .…”
Section: Introductionmentioning
confidence: 99%
“…This therapy was found to be superior when compared to synthetic odors. Synthetic fragrances generally contain irritants, like solvents and propellants causing irritation in some people [23][24][25]. According to aroma therapists, synthetic odor does not match the importance of essential oils as they are deficient in natural or vital energy; however, this has been remained a matter of debate between odor psychologists and biochemists [26] .…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated no difference in lung function between exposed and control participants and a non-significant trend in airways inflammation in the moderate asthmatics. Moderate asthmatics showed more persistent nasal symptoms (Vethanayagam et al, 2013). While this study observes no significant clinical events after exposure, issues with the study design, including small sample size, the unblinded nature and no listed exposure concentration, leave remaining questions.…”
Section: Presentationsmentioning
confidence: 78%
“…In another study, no differences in lung function were found among nonasthmatic and asthmatics exposed to an aerosolized scented product [9,56]. In another study, fragrances did not cause type 2 allergic sensitization in the respiratory tract [9,57].…”
Section: Respiratory Effects: Asthma and Other Mucosal Symptomsmentioning
confidence: 99%